Design, Manufacturing and characterization of integrated inductors with magnetic layers for DC-DC converter - Yaya, D.; Allassem, D.; Youssouf, M.; Siblini, A.; Chatelon, J. P.; Rousseau, J. J. (Advanced Electromagnetics, 2012)
This paper presents the conception, fabrication and characterization of integrated inductors containing magnetic layers. We require different steps of micro-technologies: preparation of glass and ferrite substrates, RF sputtering, photolithography, etching and finally electroplating techniques for copper and gold films. The geometrical magnitudes are determined by using HFSS simulator software. The measurements performed at low and high frequencies (up to 1 GHz) permit to verify the correlation between experiment and simulation results. The inductance of the manufactured spiral inductor is about 200 nH and it is constant from low frequency up to 0.9 GHz.